Suppressed competitive exclusion enabled the proliferation of Permian/Triassic boundary microbialites. (20th November 2019) - Foster, William J.; Heindel, Katrin; Richoz, Sylvain; Gliwa, Jana; Lehrmann, Daniel J.; Baud, Aymon; Kolar‐Jurkovšek, Tea; Aljinović, Dunja; Jurkovšek, Bogdan; Korn, Dieter; Martindale, Rowan C.; Peckmann, Jörn
Abstract: During the earliest Triassic microbial mats flourished in the photic zones of marginal seas, generating widespread microbialites. It has been suggested that anoxic conditions in shallow marine environments, linked to the end‐Permian mass extinction, limited mat‐inhibiting metazoans allowing for this microbialite expansion. The presence of a diverse suite of proxies indicating oxygenated shallow sea‐water conditions (metazoan fossils, biomarkers and redox proxies) from microbialite successions have, however, challenged the inference of anoxic conditions. Here, the distribution and faunal composition of Griesbachian microbialites from China, Iran, Turkey, Armenia, Slovenia and Hungary are investigated to determine the factors that allowed microbialite‐forming microbial mats to flourish following the end‐Permian crisis. The results presented here show that Neotethyan microbial buildups record a unique faunal association due to the presence of keratose sponges, while the Palaeotethyan buildups have a higher proportion of molluscs and the foraminifera Earlandia . The distribution of the faunal components within the microbial fabrics suggests that, except for the keratose sponges and some microconchids, most of the metazoans were transported into the microbial framework via wave currents. The presence of both microbialites and metazoan associations were limited to oxygenated settings, suggesting that a factor other than anoxia resulted in a relaxation of ecological constraints following the mass extinction event. It is inferred that the end‐Permian mass extinction event decreased the diversity and abundance of metazoans to the point of significantly reducing competition, allowing photosynthesis‐based microbial mats to flourish in shallow water settings and resulting in the formation of widespread microbialites. Abstract : After the end‐Permian mass extinction, microbialites filled the ecological niche previously occupied by metazoan reefs. The factors that allowed microbialite‐forming microbial mats to flourish are, however, hotly debated. By investigating the faunal composition and depositional setting of Permian/Triassic boundary microbialites, we propose that the impact of the extinction event on the abundance of metazoans suppressed the biological controls that were previously excluding microbialite development from subtidal environments.